Consequences of calamities and their management The case of COVID-19 pandemic and flooding on inland capture fisheries in Kenya - Aura, Christopher Mulanda (Journal of Great Lakes research, 2020)
© 2020 International Association for Great Lakes Research. Published by Elsevier B.V. All rights reserved.